Pembelajaran Bahasa Arab Berbasis Kata Serapan Bahasa Indonesia dari Bahasa Arab - Moh. Amin Santosi (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract: In the sound system between Arabic and Indonesian languages have similarities and differences. Thus, students do not always meet with difficulties in reading ora saying the words in Arabic, if they are expected to Arabic words of similar sounds in words in the Indonesian language. Therefore, the use of Arabic words tahat have been absorded by the Indonesia will be much help in learning Arabic. There are three things that will be discussed in this paper: First, the design of the use of absorption from the Arabic word as the Arabic language learning materials in school. Second, methods that can be applied in learning Arabic word-based absorption. Third, Examples of implementation measures based learning Arabaic word absorption. Keywords: Vocabulary, similarities, differences, difficultties, election